The Role of Inflammatory and Nutritional Indices as a Predictive Markers in Multiple Myeloma Patients in the Egyptian Population - Nooh, Hend A.; El-Shazly, Samar S.; Nabawy, Safa Mohamed; Elnaggar, Ghada Nabil; Abo-Elazm, Omnia M.; Shahin, Ghada Nabil (Asian Pacific Journal of Cancer Biology, 2026)
Purpose: Multiple myeloma (MM) is a malignant proliferation of plasma cells which lead to a profound health affection. Materials and Methods: 130 NDMM patients were included in this retrospective analysis. Patients’ clinico-pathological parameters, seven nutritional and inflammatory parameters were particularly noteworthy for investigation and correlation with disease stage, patient survival, and outcome. Results: 53 patients (40.8%) were female, 77 patients (59.2%) were male, and the median patient age was 56.5 (47.8-64.0) years. High TLC count, pronounced anemia, and rouleaux development were all statistically significantly associated with R/ISS stage III (P=0.003), P=0.001), and P=0.010), respectively. Serum creatinine levels, low eGFR, elevated LDH, hypoalbuminemia, elevated phosphate, elevated B2 microglobulin were all significantly correlated with R/ISS stage III (P=0.001), (P=0.001), (P=0.001), (P=0.001), (P=0.001), and (P=0.002), (P=0.001), (P=0.001), respectively. The analysis of inflammatory and nutritional indices revealed that R/ISS stage I is linked to low NLR, high PNI index, and high AAPR (P=0.013), (P=0.021), and (P=0.027), respectively, while R/ISS stage III is linked to an elevated iP/L ratio (P=0.014). Low PLR is also linked to R/ISS stage III, however the difference was not statistically significant. Following a 21-month follow-up, the cumulative OS is 37.7%, and the median OS is 29.2 months with 95% CI (22.65-35.75). Patients with low PNI and those with high NLR have worse OS (P=0.014 and P=0.029), respectively. Cox regression Multivariate analysis showed that elevated NLR is considered an independent predictor of worse overall survival. Conclusion: The study findings highlight the prognostic relevance of systemic inflammation and nutritional status in survival outcomes of NDMM patients.